A Qualitative Study: NICU Nurses as NICU Parents. (February 2016) - Fishering, Renee; Broeder, Jennifer L.; Donze, Ann
Abstract : Background: The neonatal intensive care unit (NICU) nurse who has become a NICU mother is in a unique position to evaluate the NICU experience. Because of her professional experience, she has an understanding of the NICU and healthcare environment. Purpose: This study examines the lived experiences of these women, how they coped with their roles as professionals and parents, and how their responses differed from those of NICU mothers without professional NICU experience. Methods: A narrative qualitative design was utilized to examine the lived experiences of study participants. Face-to-face taped interviews were conducted. Responses were transcribed, then analyzed using both computer-assisted data analysis and manual analysis. Results: Six nurses participated. Their responses were grouped into 6 categories on the basis of previous research. These participants experienced many of the same issues as NICU mothers without professional experience. However, there were meaningful differences. NICU nurses were vocal advocates from the first day of admission. They were also knowledgeable about how to negotiate and work around the system. Implications for Practice: NICU nurses who have had the experience of having an infant in the NICU have seen the healthcare system from both sides and can be advocates for family-centered care, helping their coworkers understand what works and what does not work for NICU families. Implications for Research: Qualitative research focused on the experiences of healthcare team members who utilize the healthcare system as patients or family members can provide an articulate and educated insight into the experiences of all who use the healthcare system. Abstract : Supplemental Digital Content is Available in the Text.